Facial flushing on upper limb exertion: a rare presentation of superior vena cava obstruction. Issue 3 (25th January 2018) - Plunkett, Michael; Wethasinghe, James; O'Donoghue, Brendon; Lever, Nigel; Wong, Conroy
Abstract : Infection remains a significant problem for patients with cardiac‐implantable electronic devices (CIEDs) but can be difficult to diagnose. We describe an unusual presentation of CIED infection in a patient with abandoned pacemaker leads. A 27‐year‐old male presented with facial flushing on upper but not lower limb exertion due to superior vena cava (SVC) obstruction, as well as pleuritic chest pain due to septic emboli. This was successfully treated with antibiotics and complete endovascular extraction of the pacemaker leads. Upper limb exertional facial flushing may be a useful clinical sign for the diagnosis of SVC obstruction. This case report also describes a rare presentation of CIED infection. Abstract : A 27‐year‐old male with infection of abandoned pacemaker leads presented with facial flushing on upper limb exertion due to superior vena cava (SVC) obstruction, as well as pleuritic chest pain due to septic emboli. Upper limb exertional facial flushing may be a useful clinical sign for the diagnosis of SVC obstruction.